2018
DOI: 10.1088/1361-6455/aad130
|View full text |Cite
|
Sign up to set email alerts
|

Looking inside the tunnelling barrier: I. Strong field ionisation from orbitals with high angular momentum in circularly polarised fields

Abstract: Here and in the two companion papers we use time-dependent analytical R-Matrix (ARM) theory to consider the impact of electron-core interaction on (i) sensitivity of strong field ionisation to the sense of electron rotation in the initial state and (ii) electron spin polarisation. ARM is a rigorous approach to strong field ionisation that takes advantage of the semiclassical nature of electron dynamics in strong laser fields and naturally incorporates complex-valued classical trajectories in the timepropagatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…In both one-photon ionization and ionization from Rydberg states of hydrogen by microwave fields [71,72], it is well known that a circularly-polarized field preferentially ionizes corotating electrons. On the other hand, recent studies [2][3][4][5][6][7][8] have established that counter-rotating electrons are preferentially ionized in the strong-field regime.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both one-photon ionization and ionization from Rydberg states of hydrogen by microwave fields [71,72], it is well known that a circularly-polarized field preferentially ionizes corotating electrons. On the other hand, recent studies [2][3][4][5][6][7][8] have established that counter-rotating electrons are preferentially ionized in the strong-field regime.…”
Section: Resultsmentioning
confidence: 99%
“…Such behaviour is in fact prevalent in ionization of p electrons from noble gases, and has been demonstrated in Ref. [2] for ionization of 4p electrons in Kr, and in subsequent studies for a variety of atomic targets exposed to fewcycle pulses [5][6][7]. The relative contributions of counter-rotating and corotating electrons are commonly quantified using their energy-dependent ratio, ρ, which PPT and ARM theories provide in the convenient form…”
Section: F Comparison With Analytical Expressionsmentioning
confidence: 91%
“…We found that the mechanism and the sign of the forwardbackward asymmetry in PECD in the regime of strong field ionization can be understood as the result of the interplay of two propensity rules: (i) the strong field ionization rate depends on the relative rotation directions of the electric field and the bound electron, being higher when the electron and the electric field rotate in opposite directions 15,16,[18][19][20]24,27 (ii) The 'forward-backward' asymmetry depends on the direction of the current of the initial state in the region of the tunnel exit, the photoelectron is more likely to be emitted 'forwards' ('backwards') if the probability current of the initial state in the tunnel exit region points 'forwards' ('backwards'). Propensity rule (i) is reversed in the high energy tail of the photoelectron spectrum, which leads to a reversal of the PECD in that region, in agreement with recent experiments 11 and simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing such initial-state specificity requires a more detailed investigation but if confirmed it would simplify the interpretation of ultra-fast chiral imaging experiments and state-of-theart simulations. That investigation could make use of the analytical R-matrix formalism, [30][31][32][33][34][35][36] which has been shown to be very accurate and would include the molecule-induced anisotropy in the photoelectron states through the Eikonal-Volkov approximation. 37 The binding potential introduced in this formalism could be modelled as a minimal chiral version with an angular dependence mimicking that of the initial wave function considered here, i.e.…”
Section: Is © the Owner Societies 2022mentioning
confidence: 99%
“…The first two can be increased by optimizing the ionizing laser parameters, drive beam parameters, and the beam loading within the wake. The latter may be increased by using electrons in the d or f orbitals instead of p orbitalsfor instance by using Yb III [41,42]. A modified version of this scheme may also be useful for generating a spinpolarized electron beam in a laser wakefield accelerator (LWFA) [43].…”
mentioning
confidence: 99%